Possible impacts of Tren Maya: The residents of Chetumal’s perspective, Quintana Roo, Mexico - Ramírez-Hernández, Omar I.; Barrón Arreola, Karla Susana; Cruz Jiménez, Graciela (Turyzm/Tourism, 2025)
The aim is to analyze the possible impacts of the Tren Maya megaproject on the city of Chetumal, Quintana Roo, Mexico, through the perceptions of its residents. The theoretical framework used is that of social representations, as this approach helps understand how people organize, interpret and give meaning to information in their environment. The methodology is qualitative, involving surveys and in-depth interviews with residents of the study area. The analysis of the results is based on trends and excerpts from interviews that illustrate and contrast the impacts perceived by the local community. The main findings indicate that Tren Maya is viewed as an opportunity for economic improvement and will invigorate the production and tourist activities of Chetumal, however negative impacts on the environment are acknowledged. It is concluded that social representations can assist in creating comprehensive strategies to mitigate potential negative impacts and enhance the benefits from the implementation of Tren Maya in Chetumal.